Instruction provider: developing a web application for giving classroom phrases in foreign languages / Yumie Murata - Murata, Yumie (2023)
This innovation is a web application as to provide classroom phrases and instructions in foreign languages for use in Japanese language classes provided by local municipalities and supported by volunteer teachers. It can also be used for children enrolled in kindergartens or primary schools who do not understand Japanese. As the application can be created using a no-code tool used worldwide, it is simple and free for anyone to create, allowing teachers to customize it according to their needs. The application can also be distributed freely among colleagues. As globalization progresses, the number of foreign residents in Japan increases and their backgrounds vary. It is important to learn Japanese to live in Japan, but children who are suddenly enrolled in local kindergartens or primary schools without knowing Japanese may face difficulties until they have learned Japanese to some extent. Teachers may be able to speak English, but English may not suffice as a language medium since the native languages of the children vary. Some teachers try to translate their speech using translation devices or smartphone applications; however, these methods are not always available in the classroom. Unfortunately, the number of classroom phrases and instructions that are crucially important at the beginning of teaching is limited. This proposed application provides the audio of these instructions in foreign languages. It is thus hoped that this application will help teachers start classes without hesitation and encourage more volunteers to participate in teaching Japanese, thereby enhancing cultural exchange in the community. The application is not intended for commercialization because it focuses on the importance of free distribution for everyone. However, it is open to everyone to create a better application that can be commercialized in the near future.